Correction of negative attitudes of athletes swimmers - Nizhnik, G.N.; Budyakova, T.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identifying the specifics of anti-victim attitudes among athletes of non-contact sports (on the example of swimming) and determining ways to correct them. Methods and structure of the study. The method of expert assessments was used as a method. The current and for- mer swimming coaches, consisting of 20 people, acted as experts. The material of the study was the lists of ineffective and productive psychological attitudes that contribute to overcoming negative factors in sports activities. Results and conclusions. It was found that, in general, the content of ineffective attitudes among athletes of contact and non-contact sports is the same, especially in terms of their victimological component, when the athlete's feelings are due to unsuccessful performances. A serious factor in the victimization of athletes is the dominance of perfectionist at- titudes.